Hubungan Antara Prokastinasi Akademik dengan Perilaku Mencontek pada Siswa SMK “X” Yogyakarta - Miftahul Hasanah; Zidni Immawan Muslimin (Jurnal Psikologi Integratif, 2016)
The purpose of this study was to determine the relationship between academic procrastination and cheating behavior on the students of Vocational High Schools “X” Yogyakarta. The hypothesis proposed that there was a positive relationship between academic procrastination and cheating behavior of students, the higher of the academic procrastination will result also to the higher of cheating behavior. As subject of this research are the class of XA, XB2, XIA, XI B2 and XI B3 students of Vocational High Schools “X” Yogyakarta, with the total amount of those are 70 students. The method of this research is quantitative. The data is from the measuring with academic procrastination scale and cheating behavior scale. The analysis technique used is the Pearson Product Moment test used SPSS version 15.0. The result obtained it shows that there was very significant and positive correlation between academic procrastination and cheating behavior on the students of Vocational High Schools “X” Yogyakarta with the value of correlation coefficient 0.461 and p = 0.000 (p < 0.01), so this hypothesis is accepted.